ANALISIS FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT LAMONGAN MENJADI NASABAH BANK SYARIAH - Maulidiyah, Musaidatul; Khoiriyah, Eva Zunia; Putri, Diva Carrisa; Nurafini, Fira (Universitas Negeri Surabaya, 2024)
Sharia banking still has problems, one of which is the lack of public knowledge about sharia banking, as evidenced by the large number of people who still use conventional banks and personal banking (daily banking) for transactions. Therefore, this research was conducted to determine the influence of knowledge, religiosity and social environment on the Lamongan community's interest in becoming sharia bank customers. This research uses a quantitative type of research with an associative approach. The sampling technique uses purposive sampling. Data analysis uses multiple correlation analysis tests, namely, T test, F test, determinant coefficient test (R2). The population of this study consisted of 100 residents of Lamongan and were used as samples. Based on the results of a simple regression test, it is known that the variables of knowledge, religiosity and social environment have a positive and significant effect on the Lamongan community's interest in becoming sharia bank customers. This is proven by the results of t-count being greater than t-table which has values of 2.137, 6.429, and 2.350 and ttable of 1.984. It was also stated that simultaneously there was a positive and significant relationship between the variables of knowledge, religiosity and social environment on the Lamongan community's interest in becoming sharia bank customers with the Fcount result being greater than Ftable, namely 18.540 > 3.09.